Grouped evaluation of Sport Canada programs: Sport Support Program, Hosting Program, Athlete Assistance Program (2010-11 to 2014-15) and review of the Federal Government Investment in Toronto 2015 Pan and Parapan American Games (2016)
Sport Canada (SC) is the single largest funder of the Canadian sport system, which is made up of a number of organizations that provide sport programming and services at the national, provincial/territorial, and municipal level. SC has an overall mission "to enhance opportunities for all Canadians to participate and excel in sport". SC delivers its support to the sport system primarily through three funding programs — the Sport Support Program (SSP), the Athlete Assistance Program (AAP), and the Hosting Program (HP). This report presents the findings on the grouped evaluation of the three sport funding programs.